Elite dan Birokrasi Pemerintahan di Indonesia - Ari Indrayono Mahar (Magister Administrasi Publik, 1998)
In the new Order era, the government had notoriously created a very centralistic and mechanistic bureaucracy consisting of counterfeit autonomy from central down to the local bureaucracy. On the other side, Indonesian culture with its paternalistic pattern has been a fertile domain for primordialism in the bureaucracy. This condition are conducive for a systematic patron-client relationship between elites and political power which applies in every stage of governmental hierarchy down to the local areas. By all means, what exist in rural-local government is no less than a representative of what happens in central government. Even after the New Order regime stepped down, the local-rural government have to dance between the central government and the local community. It appears that it would be difficult to eliminate the influence of New Order paradigm as it had been socialized and implemented for 32 years.